Formulation Aroma Therapy Balm Preparations Combination Red Ginger Essential Oils (Zingiber officinale Roscoe) and Essential Oil Of Leaves Lemongrass (Cymbophogon nardus (L) Rendle) - Sari, Melia; Chan, Adek; Faisal, Hendri; Tarigan, Rida Evalina; Nadeak, Eva Rosalina (International Journal of Health Engineering and Technology, 2024)
The essential oil combination of red ginger (Zingiber officinale Roscoe) and citronella leaves (Cymbophogon nardus (L.) Rendle) can be formulated as the most preferred balm and concentration preparation. Method type of experimental research. Experimental research is an experimental activity which aims to determine a symptom or influence that arises as a result of certain treatments. It was found in the organoleptic test that the preparation was in semi-solid form, dark yellow to pale yellow in color, with the aroma of mint and red ginger combined with citronella; the preparation is declared homogeneous; the pH of the aromatherapy balm with a combination of red ginger and citronella essential oils ranges from 5.23 – 5.63; the preparation does not cause irritation; and in the respondent's preference test, the F1 formula is more preferred. The essential oils of red ginger and citronella leaves with concentrations of 2.5%, 5%, 7.5% and 10% can be formulated into balm preparations. Test homogeneity and pH according to standars, there was no irritation in volunteers and the most popular balm preparation is formula F1 (containing 10% red ginger essential oil and leaves citronella concentration 2.5%).